Rapid Strategic Environmental Assessment of Coffee Sector Reform in Burundi - World Bank (Washington, DC, 2013)
A reform in Burundi's coffee sector is currently under way. Even though the reform was launched by the government of Burundi in 1992, it was only in 2008 that implementation fully started. The purpose of the reform is to restructure the coffee sector, focusing on the following processes: privatization of the industrial units (especially washing and hulling units), liberalization of government control among the production and export agencies, and reform of the state coffee institutions. To improve the reform process, a Rapid Strategic Environmental Assessment (R-SEA) was recommended. The goal of this RSEA is to analyze the environmental and socioeconomic aspects along the entire coffee value chain to provide strategic direction for the sustainability of coffee production, processing, and commercialization. This report is divided into six sections: (i) introduction; (ii) a description of Burundi's coffee sector; (iii) a brief explanation of the reform in the coffee sector; (iv) a description of the environ environmental and socioeconomic issues and gaps in the coffee sector, as well as recommendations for addressing them; (v) an action plan outlining priority activities to be developed in the short and medium term, and (vi) conclusions.